(untitled) (Circe de clásicos y modernos, 2025)
This paper aims to analyze, on the one hand, the construction of the chorus of Seneca’s Phaedra from two main elements, namely, movement and appearances; and, on the other hand, the way in which these elements allow establishing a correlation with the development of the plot. To this end, we focus on the visual imagery employed by Seneca and the role it plays both for the characterization of the characters and for the progression of the narrative.